Effect of thiobencarb formulations on freshwater shrimp, macrobrachium lanchesteri (De Man) - Omar, Dzolkhifli; Mohamad, Rosli (Universiti Putra Malaysia Press, 1996)
The effect of com-cob controlled-release formulations (CRF) of thiobencarb ( TAl and T A2) and alginate CRF (TAL 70192) to the freshwater shrimp, Macrobrachium lanchesteri (De Man), in comparison to a conventional granular formulation was studied in the laboratory. Mortality ofthe shrimps 24 h after exposure to the conventional formulation was significantly higher (P <= 0.05), and increased to 93.3% after 120 h. The CRF of TAl, TA2 and TAL 70192 caused mortality of 19.2,5.8 and 8.5%, respectively, 120 h after exposure. This difference is due to the slower release of thiobencarb using CRF.